Exploring variations and influencing factors of illegal adoption: A comparison between child trafficking and informal adoption. (June 2023) - Zhou, Junjun; Li, Gang; Wang, Jiaobei; Xu, Tingting; Nie, Qifan; Gao, Xing; Jin, Annan
Abstract: Background: Illegal adoption, which mainly includes child trafficking and informal adoption, has long been a prevalent social issue in China. However, the processes and patterns of illegal adoption are not well understood due to the scarcity of data. Objective: The findings are expected to provide insightful clues for the government and the public to better understand the two categories of illegal adoption. Participants and setting: This study included 4296 trafficking cases and 4499 informal adoption cases between 1949 and 2018. The data came from the 'Baby Coming Back Home' (https://www.baobeihuijia.com ) website, which is the most comprehensive commonweal forum established by nongovernmental volunteers for finding missing persons in China. Methods: Mathematical statistics and hot spot analysis were used to visualize the spatiotemporal pattern of illegal adoption. Results: Child trafficking and informal adoption show opposite gender preferences and different age gradients. The numbers of both cases peaked in the early 1990s and then dropped. More than 50 % of all trafficked children were male, whereas approximately 83 % cases of informal adoption were female between 1980 and 2000. Hot spots of illegal adoption have shifted from the cities of the Huai River Basin to the southeastern coastal cities over time, 39.40 % of trafficking cases occurred in rural residential areas, and 52.45 % of informal adoption cases were observed in hospitals. Conclusions: Child trafficking and informal adoption are two different ways of adopting children in China. The combination of the one-child policy and the traditional culture of son preference shaped the different characteristics of the illegal adoption of children during a critical period. Highlights: Child trafficking and informal adoption show opposite gender preferences and different age gradients. More than 50 % of all trafficked children were male, whereas approximately 83 % cases of informal adoption were female between 1980 and 2000. Hot spots of illegal adoption have shifted from the cities of the Huai River Basin to the southeastern coastal cities over time. The combination of the one-child policy and the traditional culture of son preference shaped the different characteristics of the illegal adoption of children during a critical period.